2017
DOI: 10.1016/j.physleta.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of a classical short-range spin model with a phase transition in one dimension: The Potts model with invisible states

Abstract: We present the exact solution of the 1D classical short-range Potts model with invisible states. Besides the q states of the ordinary Potts model, this possesses r additional states which contribute to the entropy, but not to the interaction energy. We determine the partition function, using the transfer-matrix method, in the general case of two ordering fields: h 1 acting on a visible state and h 2 on an invisible state. We analyse its zeros in the complex-temperature plane in the case that h 1 = 0. When Im h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…For systems on scalefree networks, degree distribution exponent plays similar role. In addition, invisible states have been shown to influence the universality class with only changing entropic contribution to the free energy [15,16]. As was shown in this paper, with these two mechanisms together, the Ising model exhibits non-trivial properties.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For systems on scalefree networks, degree distribution exponent plays similar role. In addition, invisible states have been shown to influence the universality class with only changing entropic contribution to the free energy [15,16]. As was shown in this paper, with these two mechanisms together, the Ising model exhibits non-trivial properties.…”
Section: Discussionsupporting
confidence: 52%
“…This model was originally suggested to explain why the phase transition with the q−fold symmetry breaking undergoes a different order than predicted theoretically [7,8,9]. Analysis of this model on different lattices has been a subject of intensive analytic [10,11,12,13,14,15,16] and numerical [7,8,9] studies. It has been shown that the number of invisible states (r) plays the role of a parameter, whose increase makes the phase transition sharper.…”
Section: Introductionmentioning
confidence: 99%
“…Although few one-dimensional models exhibit the phase transition [4][5][6][7], this phenomenon is related to some null elements of the transfer-matrix, which leads to a non-analytic free energy. Nevertheless, pseudo-critical temperatures have recently been investigated in onedimensional spin models [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Dauxois-Peyrard model [6], is another model with infinite transfer-matrix dimension, which can be solved numerically. More recently Sarkanych et al [7] also proposed a one-dimensional Potts model with invisible states and short-range coupling. The term invisible essentially refers to an additional energy degeneracy, which contributes to the entropy, but not the interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…The second law of thermodynamics tells us that entropy increases -you can't add negative entropy. (Actually you can, but that's another story [54].) I propose the second law of impact is enlightenment via media is not negative.…”
Section: Fundamentals Of the Laws Of Impactmentioning
confidence: 95%